Implementation av C-moduler för utveckling av mobila applikationer i Android - Olsson, Henrik; Zilaei, Ehsan (My University, 2011)
In todays society mobile applications have become very popular, which has lead to an overwhelming amount of applications for several different purposes on the market. As a result, their has been a rapid acceleration of the demands regarding programmers and their ability to cope with the high development speed that is needed due to existing competition. In this thesis we will investigate the possibilities to, in an efficient way, make use of the C-support that could be found in most modern platforms, with the goal of developing C-code which is platform-independent. As example of implementation the Android-platform will be used and we have constructed an model of how such an implementation can look like. Also, important factors like performance and benefits/drawbacks will be covered for this platform. We will also evaluate when an implementation like this is suitable and how it is achieved.
Keywords: Informations- och kommunikationsteknik; Programvaruteknik; Information & Communication Technology; Software Engineering